The Nellie stories - Matthews, Penny 1945- (Viking, 2016)
It's 1849 and Nellie O'Neill has arrived in South Australia on a ship bringing orphan girls from Irish workhouses. She has left the famine in Ireland far behind, and is full of hopes and dreams for the future. She wants to learn to read, to be part of a family once more and never to be hungry again. Can Nellie make her wishes come true?Join Nellie across all four stories about an Irish girl with a big heart, in search of the freedom to be herself. Brave, adventurous, loyal and clever, Nellie is a remarkable Australian Girl. Ages 13+
4 books in one
Keywords: Children's stories